Hypoxanthine-Guanine Phosphoribosyltransferase/adenylate Kinase From Zobellia galactanivorans: A Bifunctional Catalyst for the Synthesis of Nucleoside-5′-Mono-, Di- and Triphosphates - Acosta, Javier; Del Arco, Jon; Del Pozo, Maria Luisa; Herrera-Tapias, Beliña; Clemente-Suárez, Vicente Javier; Berenguer, José; Hidalgo, Aurelio; Fernández-Lucas, Jesús (Frontiers in Bioengineering and Biotechnology, 2020)
In our search for novel biocatalysts for the synthesis of nucleic acid derivatives, we found a good candidate in a putative dual-domain hypoxanthine-guanine phosphoribosyltransferase (HGPRT)/adenylate kinase (AMK) from Zobellia galactanivorans (ZgHGPRT/AMK). In this respect, we report for the first time the recombinant expression, production, and characterization of a bifunctional HGPRT/AMK. Biochemical characterization of the recombinant protein indicates that the enzyme is a homodimer, with high activity in the pH range 6-7 and in a temperature interval from 30 to 80 ºC. Thermal denaturation experiments revealed that ZgHGPRT/AMK exhibits an apparent unfolding temperature (Tm) of 45 ºC and a retained activity of around 80 % when incubated at 40 ºC for 240 min. This bifunctional enzyme shows a dependence on divalent cations, with a remarkable preference for Mg2+ and Co2+ as cofactors. More interestingly, substrate specificity studies revealed ZgHGPRT/AMK as a bifunctional enzyme, which acts as phosphoribosyltransferase or adenylate kinase depending upon the nature of the substrate. Finally, to assess the potential of ZgHGPRT/AMK as biocatalyst for the synthesis of nucleoside-5´-mono, -di and triphosphates, the kinetic analysis of both activities (phosphoribosyltransferase and adenylate kinase) and the effect of water-miscible solvents on enzyme activity were studied.